Twice Have the Trumpets Sounded - Carlson, Marvin (Recherches sémiotiques / Semiotic Inquiry, 2015)
Probably no single aspect of the semiotics of performance is more critical than the conventionalized signals that inform the audience that they are entering or leaving the liminal world of performance, and that the signs they will receive between these two signals are to be interpreted not necessarily as they would be in everyday life, but according to the codes of the performance situation. A clear example of one familiar modern sign for the ending of the performance is, of course, the curtain call. Throughout the history of theatre, the ending of the performance has most commonly been signaled by visual means – the curtain call, the bringing up of the house lights, the lowering of the house curtain, the general dance of the performers. When we consider the various means by which the beginning of a performance is indicated, however, we find that a significant number of them are in fact not visual but sonic – the first, second and third music in Restoration theatre, the trumpet fanfares at Stratford (Ontario) the “trois coups” of the traditional French theatre, the traditional playing of “God Save the Queen” in British theatres, and Ellen Stewart’s ringing of the hand bell for years at La Mama. In certain cases, the semiotics of sound have been prioritized over those of sight for the sake of summoning audiences, but most often they are already assembled and so other dynamics are at work. This essay will consider some of the most important uses of sound in this particular semiotic function, that is, as a signal for the audience to experience various theatrical works with a performance-oriented consciousness.